The Effect of Drill Methods on Students’ Football Passing Skills in SSB Bangsal Putra - Maskun, Muhamad Arifin; Yuliawan, Dhedhy; Purnomo, Ardhi Mardiyanto Indra (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This study aims to identify the effect of the El Rondo Drill and Wallpass Drill training methods on students’ football passing skills in SSB Bangsal Putra. This study used a quantitative descriptive method. The population of this study was all students in SSB Bangsal Putra aged 10-12 years totaling 28 people. Sampling was conducted using Matched Subject Ordinal Pairing (MSOP) with the pattern A-B-B-A into two groups that had the same number of members. The selection of samples used a non-probability sampling technique, namely saturated sampling. The results of the analysis showed that (1) the El Rondo drill and Wallpass drill training methods positively and significantly improved students' passing skills. The t-count value for the El Rondo drill was 9,200 which was higher than the t-table value of 2.04841 with Sig. (2-tailed) 0.000 <0.05, indicating an increase of 80.65%. (2) The Wallpass drill had a t-count value of 11,845 which was higher than the t-table value of 2.04841 with Sig. (2-tailed) 0.000 < 0.05, indicating an increase of 75%. It can be concluded that the El Rondo drill method is more effective than the Wallpass drill method in improving the students’ passing skills in SSB Bangsal Putra.